ANALISIS TECHNOLOGY ACCEPTANCE MODEL (TAM) PADA GURU RA KOTA MALANG - Ayu Putri Rizki; Mutiara Sari Dewi; Ari Kusuma Sulyandari (Jurnal Dewantara, 2022)
During the Covid-19 pandemic, learning was not carried out directly because it was too risky to apply. At this time, learning is done in a network so that the need for the internet is increasing. This situation requires teachers to understand the internet so that learning continues to run smoothly. One way to address this is by applying the Technology Acceptance Model (TAM). This study aims to describe the demographics and TAM profile of RA teachers in Malang City. This research is a type of qualitative research. The population is RA teachers in Malang City, while the sample in this study is 5 RA schools in Malang City. The results of the demographic research of RA teachers in the city of Malang proved that the average RA teacher in the city of Malang had an undergraduate education background (S1). The average RA teachers in Malang City agree that the internet is easy to use and can simplify their work and can improve their performance to support them as professional educators and the use of the internet is also considered flexible so it is easy to use at all ages.